Evolving View of Coronary Artery Calcium: A Personalized Shared Decision-Making Tool in Primary Prevention - Omar Dzaye; Cara Reiter-Brennan; Albert D. Osei; Olusola A. Orimoloye; S. M. Iftekhar Uddin; Mohammadhassan Mirbolouk; Michael J. Blaha (Cardiology Research and Practice)
The 2018 American Heart Association and American College of Cardiology (AHA/ACC) cholesterol management guideline considers current evidence on coronary artery calcium (CAC) testing while incorporating learnings from previous guidelines. More than any previous guideline update, this set encourages CAC testing to facilitate shared decision-making and to individualize treatment plans. An important novelty is further separation of risk groups. Specifically, the current prevention guideline recommends CAC testing for primary atherosclerotic cardiovascular disease (ASCVD) prevention among asymptomatic patients in borderline and intermediate risk groups (5–7.5% and 7.5–20% 10-year ASCVD risk). This additional subclassification reflects the uncertainty of treatment strategies for patients broadly considered to be “intermediate risk,” as treatment recommendations for high- and low-risk groups are well established. The 2018 guidelines, for the first time, clearly recognize the significance of a CAC score of zero, where intensive statin therapy is likely not beneficial and not routinely recommended in selected patients. Lifestyle modification should be the focus in patients with CAC = 0. In this article, we review the recent AHA/ACC cholesterol management guideline and contextualize the transition of CAC testing to a guideline-endorsed decision aid for borderline- to intermediate-risk patients who seek more definitive risk assessment as part of a clinician-patient discussion. CAC testing can reduce low-value treatment and focus primary prevention therapy on those most likely to benefit.